Multiple Myeloma in a Patient with ANKRD26-Related Thrombocytopenia Successfully Treated with Combination Therapy and Autologous Stem Cell Transplant. (2nd June 2019) - Husnain, Muhammad; Wang, Trent; Valdes, Maikel; Hoffman, James; Lekakis, Lazaros
Abstract : Ankyrin repeat domain-containing protein 26- (ANKRD26-) related thrombocytopenia is a rare, autosomal dominant condition caused by ANKRD26 gene mutation. ANKRD26-related thrombocytopenia is characterized by moderate thrombocytopenia with minimal bleeding, normal platelet size, and dysmegakaryopoiesis on bone marrow evaluation. ANKRD26 mutation has been previously associated with myeloid malignancies, including acute myeloid leukemia, myelodysplastic syndrome, and chronic myeloid leukemia. We report the first case of multiple myeloma in a patient with ANKRD26 related thrombocytopenia. The patient was successfully treated with contemporary combination therapy followed by melphalan-conditioned autologous stem cell transplant for his multiple myeloma despite preexisting thrombocytopenia.